(The Effect of Concentration Of The Edta (Disodium Ethylene Diamine Tetra Acetic Acid) and The Duration of Agitation on Chelation of Iron Ion in Patchuoly Oil) - Moestafa, Achmad; Suprijatna, Endang; -, Gumilar (Balai Besar Industri Agro, 1990)
The traditional dark brown patchouly oil has a pleasant odour and highly demanded in international market. Recently the colour preference has changed from dark brown to a lighter colour. Souch colour can be produced using stainless steel distillation equipment or eliminate the iron ion in the brown oil by chemical means. An experiment using Na-EDTA solution has been carried out. The result showed that the use of 0.04 and 0.05 M solution will remove 95% of the iron ion. The oil colour became yellow without affecting its olfactive properties as well as well as its physical and chemical constant